Phenylbutyrate increases pyruvate dehydrogenase complex activity in cells harboring a variety of defects. (19th June 2014) - Ferriero, Rosa; Boutron, Audrey; Brivet, Michele; Kerr, Douglas; Morava, Eva; Rodenburg, Richard J.; Bonafé, Luisa; Baumgartner, Matthias R.; Anikster, Yair; Braverman, Nancy E.; Brunetti‐Pierri, Nicola
Abstract Objective Deficiency of pyruvate dehydrogenase complex (PDHC) is the most common genetic disorder leading to lactic acidosis. PDHC deficiency is genetically heterogenous and most patients have defects in the X‐linked E1‐α gene but defects in the other components of the complex encoded by PDHB, PDHX, DLAT, DLD genes or in the regulatory enzyme encoded by PDP1 have also been found. Phenylbutyrate enhances PDHC enzymatic activity in vitro and in vivo by increasing the proportion of unphosphorylated enzyme through inhibition of pyruvate dehydrogenase kinases and thus, has potential for therapy of patients with PDHC deficiency. In the present study, we investigated response to phenylbutyrate of multiple cell lines harboring all known gene defects resulting in PDHC deficiency. Methods Fibroblasts of patients with PDHC deficiency were studied for their enzyme activity at baseline and following phenylbutyrate incubation. Drug responses were correlated with genotypes and protein levels by Western blotting. Results Large deletions affecting PDHA1 that result in lack of detectable protein were unresponsive to phenylbutyrate, whereas increased PDHC activity was detected in most fibroblasts harboring PDHA1 missense mutations. Mutations affecting the R349‐α residue were directed to proteasome degradation and were consistently unresponsive to short‐time drug incubation but longer incubation resulted in increased levels of enzyme activity and protein that may be due to an additional effect of phenylbutyrate as a molecular chaperone. Interpretation PDHC enzyme activity was enhanced by phenylbutyrate in cells harboring missense mutations in PDHB, PDHX, DLAT, DLD, and PDP1 genes. In the prospect of a clinical trial, the results of this study may allow prediction of in vivo response in patients with PDHC deficiency harboring a wide spectrum of molecular defects.